2019
DOI: 10.3390/ma12132155
|View full text |Cite
|
Sign up to set email alerts
|

Water Effects on Molecular Adsorption of Poly(N-vinyl-2-pyrrolidone) on Cellulose Nanocrystals Surfaces: Molecular Dynamics Simulations

Abstract: Models of interaction between a poly(N-vinyl-2-pyrrolidone) macromolecule and a fragment of Iβ-cellulose were built in a vacuum and water environment. The models were made to interpret the mechanism of interaction of the polymer and cellulose nanocrystals by the classical molecular dynamics method. The structural behavior of a poly(N-vinyl-2-pyrrolidone) macromolecule in water has been studied in terms of the radius of gyration, atom–atom radial distribution functions and number of hydrogen bonds. It was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…It should be noted that in our previous work devoted to studying the adsorption of PVP on CNC, we also observed the crucial role of water in the interaction between PVP and CNC [ 26 ]. In particular, we showed that the presence of water makes the interaction between the polymer and cellulose weaker than in a vacuum, and the polymer and cellulose mainly interact through their solvation shells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that in our previous work devoted to studying the adsorption of PVP on CNC, we also observed the crucial role of water in the interaction between PVP and CNC [ 26 ]. In particular, we showed that the presence of water makes the interaction between the polymer and cellulose weaker than in a vacuum, and the polymer and cellulose mainly interact through their solvation shells.…”
Section: Resultsmentioning
confidence: 99%
“…The current work is a continuation of our previous study that was devoted to the investigation of the microscopic mechanism of polyvinylpyrrolidone (PVP) adsorption on a cellulose nanocrystal and the role of water in this process [ 26 ]. We have revealed earlier [ 27 ] that PVP adsorption onto CNC can block lateral interactions between the CNC and prevents their agglomeration in the lateral direction, i.e., hinders growth of the CNC particles width upon the concentration increase or drying of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the swelling behavior of PDMAEMA brushes has been studied by using united-atom G54a7 version of the GROMOS FF . Moreover, G53a6 FF has also revealed a good performance for modeling physicochemical properties of other structurally similar polymers. ,,, …”
Section: Simulation Setupmentioning
confidence: 99%
“…This result suggested that the amount of carrier in solid dispersion might affect the zeta potential of the NE. The molecular structure of PVP possesses negative charges according to the carbonyl group and nitrogen atom of the pyrrolidone ring [ 37 ]. These negative-charge groups were considered to play an important role in increasing the negative zeta potential value.…”
Section: Resultsmentioning
confidence: 99%